Effect of long-term mineral fertilisation on soil microbial abundance, community structure and diversity in a Typic Hapludoll under intensive farming systems - Verdenelli, Romina Aylen (2019)
Fertiliser application can not only influence plant communities, but also the soil microbial community dynamics, and consequently soil quality. Specifically, mineral fertilisation can directly or indirectly affect soil chemical properties, microbial abundance and, the structure and diversity of soil microbial communities. We investigated the impact of six different mineral fertiliser regimes in a maize/soybean rotation system: control (CK, without fertilisation), PS (application of phosphorus plus sulphur), NS (application of nitrogen plus S), NP (application of N plus P), NPS (application of N, P plus S) and NPSm (application of N, P, S plus micronutrients). Soil samples were collected at the physiological maturity stage of maize and soybean in March of 2013 and 2014, respectively. Overall, mineral fertilisation resulted in significantly decreased soil pH and increased total organic carbon compared with the control (CK). The analysis of terminal restriction fragment length polymorphism (T-RFLP) revealed that mineral fertilisers caused a shift in the composition of both bacterial and fungal communities. In 2013, the highest value of Shannon diversity of bacterial terminal restriction fragments (TRFs) was found in control soils. In 2014, NPSm treated soils showed the lowest values of diversity for both bacterial and fungal TRFs. In both crop growing seasons, the analysis of phospholipid fatty acid (PLFA) detected the lowest value of total microbial biomass under CK. As PLFA analysis can be used to evaluate total microbial community, this result suggests that fertilisation increased total microbial biomass. When the bacterial and fungal abundance were examined using real time polymerase chain reaction, the results revealed that mineral fertilisation led to decreased bacterial abundance (16S rRNA), while fungal abundance (18S rRNA) was found to be increased in both crop growing seasons. Our results show that mineral fertiliser application has a significant impact on soil properties, bacterial and fungal abundance and microbial diversity. However, further studies are needed to better understand the mechanisms involved in the changes to microbial communities as a consequence of mineral fertilisation.